MARKETING STRATEGIES OF PHARMACEUTICAL ORGANIZATION - N. M. Sergeeva; E. V. Reprintseva (Фармация и фармакология (Пятигорск), 2015)
Strategy of pharmaceutical goods (PG) promotion is a working out of methods of goods realization stimulation. To make PG promotion maximum effective, and to receive a sufficient result for pharmaceutical organization (PO) it is necessary to conduct marketing studies (MS), to work out a marketing plan for PG promotion and to offer marketing strategies for goods promotion. To resolve these problems we have formed a concept of marketing promotion of PG system for one of big retail PO of Kursk and Kursk oblast (code name “A”). With this purpose we have identified a problem of PG promotion organization, studied an influence of external and internal environment on the PO “A” activity, determined strong and weak sides of PO activity. We have systematized the results in SWOT-analysis, and formed the strategies of PO for the improvement of work efficiency on the market. On the basis of the results received we have worked out the recommendations for the marketing strategies of PG promotion for the certain PO.